2015
DOI: 10.1042/bst20150044
|View full text |Cite
|
Sign up to set email alerts
|

Value of monitoring Nrf2 activity for the detection of chemical and oxidative stress

Abstract: Beyond specific limits of exposure, chemical entities can provoke deleterious effects in mammalian cells via direct interaction with critical macromolecules or by stimulating the accumulation of reactive oxygen species (ROS). In particular, these chemical and oxidative stresses can underpin adverse reactions to therapeutic drugs, which pose an unnecessary burden in the clinic and pharmaceutical industry. Novel pre-clinical testing strategies are required to identify, at an earlier stage in the development path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Nrf2, one of the most important transcription factors that activates several genes with cytoprotective function, participates in antioxidant and anti-inflammatory reactions [ 72 , 73 , 74 , 75 , 76 , 77 ]. These cytoprotective genes encode a wide variety of phase II detoxification enzymes, such as NAD (P) H: quinone oxidoreductase 1 (NQO1), HO-1, γ-GCS, glutathione S-transferase (GST) and glutamate-cysteine ligase, thioredoxin, thioredoxin reductase, thermal shock proteins and many others [ 31 , 78 , 79 , 80 , 81 ]. Cell culture studies have shown that HT was the only olive oil phenol capable of increasing the transactivation of Nrf2, which suggests that this polyphenol could be responsible for the induction of Nrf2-dependent gene expression [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, one of the most important transcription factors that activates several genes with cytoprotective function, participates in antioxidant and anti-inflammatory reactions [ 72 , 73 , 74 , 75 , 76 , 77 ]. These cytoprotective genes encode a wide variety of phase II detoxification enzymes, such as NAD (P) H: quinone oxidoreductase 1 (NQO1), HO-1, γ-GCS, glutathione S-transferase (GST) and glutamate-cysteine ligase, thioredoxin, thioredoxin reductase, thermal shock proteins and many others [ 31 , 78 , 79 , 80 , 81 ]. Cell culture studies have shown that HT was the only olive oil phenol capable of increasing the transactivation of Nrf2, which suggests that this polyphenol could be responsible for the induction of Nrf2-dependent gene expression [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2-driven response to chemical and oxidative stress has been associated with several forms of drug toxicity in pre-clinical studies 9 . Amongst ongoing efforts to reduce attrition and improve the benefit:risk balance of new drugs, there is an increasing interest in using the perturbation of Nrf2 and other stress response pathways as mechanism-based markers of toxicity 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2 signalling has been demonstrated in animals exposed to many drugs and chemical entities 9 , yet such in vivo studies have almost exclusively relied on the analysis of a single tissue relevant to the toxicological insult (e.g. our previous work showing activation of Nrf2 in the livers of mice exposed to the hepatotoxin acetaminophen 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also appears to have contrasting effects in response to viral infection as viruses activate Nrf2, which promotes their proliferation in the host [10]. Nrf2 also plays an important role in protecting against chemical toxicity and may be useful in pre-clinical testing of chemicals and drugs that may induce toxicity or adverse drug reactions [11].…”
Section: Nrf2 and Cellular Homoeostasismentioning
confidence: 99%